VALUASI OPSI SAHAM ASIA RATA-RATA ARITMATIKA DENGAN METODE BINOMIAL - Franstianto, Vincentius
In this thesis, we examine binomial method for pricing Asian stock options and Monte Carlo simulation as benchmark. Asian stock option is an option which payoff depends on the average of the stock price in some time within the lifetime of the option. In this thesis, we examine Asian stock option with arithmetic average. The arithmetic average of the stock price is taken in full time and partial time. Partial arithmetic average means the average is taken from the beginning of the lifetime until sometime before the end of the lifetime. We use CRR as model for the evolution of the stock price. Methods for valuing Asian stock option are Hull and White's method, Costabile's method and Moon's method. Differences between Hull and White's method, Costabile's method and Moon's method is on the average of the stock price. Hull and White's method and Moon's method don't use real arithmetic average. Costabile's method uses real arithmetic average. For valuing Asian stock option, all of three methods use backward induction method combined with linear interpolation. In case of Asian stock option with partial average, if the average is taken until sometime before the end of the lifetime, say it t', we use the standard backward induction method for valuing Asian stock option in the time after and at t'. We use backward induction combined with linear interpolation for valuing Asian stock option in the time before t'. By using Monte Carlo simulation as benchmark, all of three methods give accurate results. But, in terms of the rate of convergence and accuracy, Moon's method is the best method for pricing Asian stock option. Tugas